Penegakan Hukum Terhadap Selebgram yang Mempromosikan Situs Judi Online - Ignasius Yosanda Nono; Anak Agung Sagung Laksmi Dewi; I Putu Gede Seputra (Fakultas Hukum Universitas Warmadewa, 2021)
Celebgrams or the acronyms for celebrities and Instagram are those that are well known through the social media Instagram. Celebrities are not much different from celebrities in general. The difference between celebrities and celebrities in general lies only in the medium. If most celebrities are famous for their appearance on the screen, a celebrity is famous for their presence on Instagram social media. The viral figure of celebrities on Instagram is used as an opportunity for business people to endorse / promote gambling sites through the Instagram account belonging to this celeb. The formulation of the problem that can be raised is How is law enforcement regarding the promotion of online gambling sites? What are the criminal sanctions against celebrities who promote online gambling sites? This thesis uses a type of normative legal research, Law Number 11 of 2008 concerning Electronic Information and Transactions, the Criminal Code is the legal basis for knowing legal arrangements and legal sanctions against celebrities promoting online gambling sites. The results of this study indicate that the imposition of legal sanctions on celebrities.